Добро пожаловать в сказку! - Благов Владимир Иванович (Серия "Новые сказочные повести", 2010)
Экземпляры: ф. 1 (20140317) / Инвентарный номер: 100875 / Цена: 73.00 / Авт.знак: Б 68 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6